Review on Statistics (First Publish) - Tay, Choo Chuan; Sakidin, Hamzah; Sek, Yong Wee; Law, Check Yee (Penerbit Universiti Teknikal Malaysia Melaka, 2009)
One of the most challenging aspects of mathematics learning is to give students suitable examples and exercises which can improve their understanding.